2016
DOI: 10.1038/ncomms10991
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes vaccine candidates promote human Foxp3+Treg induction in humanized mice

Abstract: Immune tolerance is executed partly by Foxp3+regulatory T (Treg) cells, which suppress autoreactive T cells. In autoimmune type 1 diabetes (T1D) impaired tolerance promotes destruction of insulin-producing β-cells. The development of autoantigen-specific vaccination strategies for Foxp3+Treg-induction and prevention of islet autoimmunity in patients is still in its infancy. Here, using human haematopoietic stem cell-engrafted NSG-HLA-DQ8 transgenic mice, we provide direct evidence for human autoantigen-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 72 publications
6
123
0
Order By: Relevance
“…S10 A-C). Next, to assess a potential human in vivo relevance of miRNA92a antagomir application, we investigated human HLA-DQ8-restricted insulin-specific TFH cells in humanized NOD Scid IL2 receptor gamma chain knockout (NSG) human leucocyte antigen (HLA)-DQ8 Tg mice in accordance with previously established procedures (31). Specifically, we focused on human pancreas-infiltrating CD4 + T cells upon treatment with a miRNA92a antagomir (1 wk of treatment, with injections three times per week at 10 mg/kg) or a control antagomir.…”
Section: Cxcr5mentioning
confidence: 99%
See 1 more Smart Citation
“…S10 A-C). Next, to assess a potential human in vivo relevance of miRNA92a antagomir application, we investigated human HLA-DQ8-restricted insulin-specific TFH cells in humanized NOD Scid IL2 receptor gamma chain knockout (NSG) human leucocyte antigen (HLA)-DQ8 Tg mice in accordance with previously established procedures (31). Specifically, we focused on human pancreas-infiltrating CD4 + T cells upon treatment with a miRNA92a antagomir (1 wk of treatment, with injections three times per week at 10 mg/kg) or a control antagomir.…”
Section: Cxcr5mentioning
confidence: 99%
“…We used CD4 + T cells from nondiabetic children without autoimmunity (islet autoantibody-negative children), with recent onset of autoimmunity (recent activation, multiple autoantibodies for <5 y), persistent autoimmunity (multiple autoantibodies for >5 to <10 y), and long-term autoimmunity (multiple autoantibodies for >10 y without overt T1D). We applied recently developed fluorescent insulin-specific HLA-DQ8 tetramers (14E-22E and 14E-21G 22E tetramers) based on a set of two insulin B-chain 10-23 mimetopes to identify human HLA-DQ8-restricted insulinspecific CD4 + T cells ex vivo directly (31). We detected no tet + CD4 + T cells using the control tetramers, whereas a population of insulin-specific CD4 + T cells was readily identified ex vivo with the insulin-specific tetramers ( Fig.…”
Section: Enhancement Of Insulin-specific Cxcr5mentioning
confidence: 99%
“…S1). Given the critical role of insulin epitopes as target autoantigens, we focused on insulin-specific T reg induction using highly pure naïve CD4 + T cells and premature withdrawal of TCR stimulation after 18 hours without transforming growth factor–β (11, 12). We therefore used previously established protocols using HLA-DQ8 insulin-specific monomers coated onto streptavidin-precoated plates (12).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, high frequencies of insulin-specific T regs were associated with profound delays in progressing to symptomatic T1D (12). However, a mechanistic understanding of relevant promoters of T cell activation involved in triggering islet auto-immunity is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the loss of IAA may simply be a matter of increasing age and therefore seen in children with slow progression. Nevertheless, we have recently shown that high frequencies of insulin-specific regulatory T cells are found in multiple-autoantibody-positive children who do not progress to clinical type 1 diabetes and therefore could indicate at least periods of successful ongoing immune regulation in such children [50].…”
Section: Discussionmentioning
confidence: 99%